2017
DOI: 10.1039/c7ob01867c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of quinolines via copper-catalyzed domino reactions of enaminones

Abstract: Quinoline derivatives were obtained from enaminones and 2-bromo- or 2-iodobenzaldehydes via copper-catalyzed domino reactions consisting of the aldol reaction, C(aryl)-N bond formation and elimination. The electronic effect of aldehydes played a major role in the reaction outcome. Two simple protocols are disclosed to achieve various quinolines from both cyclic and acyclic enaminones in good yields. With the less-reactive acyclic enaminones, diethyl-2-(2-bromobenzylidene)malonate was shown to be more compatibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This process consists of copper-catalyzed Ullmann C-N coupling followed by the aldol condensation process (Scheme 30). 47 The addition of drying agent molecular sieves to the reaction medium improved the yield of the product. The reactivity of cyclic enaminones is higher in comparison with acyclic enaminones for this reaction.…”
Section: Reviewmentioning
confidence: 99%
“…This process consists of copper-catalyzed Ullmann C-N coupling followed by the aldol condensation process (Scheme 30). 47 The addition of drying agent molecular sieves to the reaction medium improved the yield of the product. The reactivity of cyclic enaminones is higher in comparison with acyclic enaminones for this reaction.…”
Section: Reviewmentioning
confidence: 99%
“…From the viewpoint of sustainable and atom-economical development, domino reactions offer the most straightforward approach for constructing heterocyclic compounds. [40][41][42][43][44][45] Satyanarayana and co-workers 46 developed a microwaveassisted Pd[0]-catalyzed domino Heck cyclization and decarboxylative Sonogashira coupling of 22 with propiolic acids 23 in water as the sole solvent in the presence of quaternary ammonium salts (Scheme 10a). This method, which involved the formation of two C-C σ bonds, overcame the homocoupling issue of terminal alkynes to deliver the desired products 24 in good to moderate yields with good functional group tolerance.…”
Section: Reviewmentioning
confidence: 99%
“…2-Halobenzaldehyde afforded dihydroacridines (78) with cyclic enaminone, and acyclic enaminones gave substituted quinoline. [41] The electronic effect in the aldehydes played a pivotal role in the reaction outcome. It was observed that electron-donating substituents gave better yield compared to electron-withdrawing ones.…”
Section: Pyridine Synthesismentioning
confidence: 99%